New Insights into the Distribution, Physiology and Life Histories of South American Galaxiid Fishes, and Potential Threats to this Unique Fauna - Cussac, Victor Enrique (2020)
South American galaxiids occupy both Patagonia and the ichthyogeographic Chilean Province, encompassing glacial Andean deep lakes, shallow plateau lakes, reservoirs, short Pacific rivers and long Atlantic rivers. The total fish fauna includes 29 species, comprising Neotropical fishes (siluriforms and characids), galaxiids, percichthyids, atherinopsids and mugilids, two lamprey species, and several exotic fishes (salmonids, Gambusia spp. and common carp). The family Galaxiidae shares a common ancestry with the Gondwanan temperate fish fauna, played a major role in the post-glacial colonization of Andean lakes and streams, and contributes key species to the food webs. Galaxiid species occupy an enormous latitudinal gradient, show a wide variety of life history patterns and are the southernmost native freshwater fishes of the world. Knowledge of South American galaxiids has improved notably, but new challenges arise due to climate change, biological invasions, damming, aquaculture and contamination. In this changing environment, the future of South American galaxiids should be carefully considered as a legacy of the old Gondwana and a unique attribute of the freshwaters of southern South America.